Nitrate assimilation in plant shoots depends on photorespiration - Rachmilevitch, Shimon (National Academy of Sciences, 2004)
Photorespiration, a process that diminishes net photosynthesis by ≈25% in most plants, has been viewed as the unfavorable consequence of plants having evolved when the atmosphere contained much higher levels of carbon dioxide than it does today. Here we used two independent methods to show that exposure of Arabidopsis and wheat shoots to conditions that inhibited photorespiration also strongly inhibited nitrate assimilation. Thus, nitrate assimilation in both dicotyledonous and monocotyledonous species depends on photorespiration. This previously undescribed role for photorespiration (i) explains several responses of plants to rising carbon dioxide concentrations, including the inability of many plants to sustain rapid growth under elevated levels of carbon dioxide; and (ii) raises concerns about genetic manipulations to diminish photorespiration in crops.